Peningkatan Pemahaman Kelembagaan Pelajar SMKN 2 Kelompok Teknologi dan Rekayasa Meulaboh - Ringo, Liston Siringo; Soufyan, Dara Angreka (Nawadeepa: Jurnal Pengabdian Masyarakat, 2025)
This Community Service (PkM) activity aims to address the lack of knowledge among vocational high school students about organizational structures required for entering the business world. By introducing students to the importance of institutions in business, the activity seeks to provide an understanding of institutional benefits and steps to establish. The approach involves delivering lectures on the definition and components of institutions, followed by a discussion on the practical steps to form an organization. Students were engaged in an interactive session where they learned about the types of institutions that can support their entrepreneurial ventures. The activity successfully increased students' awareness of the importance of institutions in business. Participants gained a better understanding of how institutions enhance bargaining power, open market opportunities, and foster collaboration among members. Students also recognized various institutional forms that can be developed to support business initiatives. This activity was limited to a single session at one vocational school, which may limit the generalizability of the findings. Future programs could involve multiple schools to gather broader insights.